Inovasi Pengelolaan Keuangan Keluarga Berbasis Android melalui Optimalisasi Fitur Aplikasi Money Manager - Bambang Wahyudi; Abdul Khafid; Kuwatno; Muarifudin; Ripan; Milatina Laksmita Dewi; Dina Ulayya Aziizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Universitas Selamat Sri, 2026)
The problem of low family financial literacy among productive communities, particularly cooperative members, remains a challenge in efforts to achieve sustainable household prosperity. This activity aims to improve family financial management skills by optimizing the use of the Android-based Money Manager application. The activity partners were members of the Buwana Karya Kendal Multipurpose Cooperative (KSU), the majority of whom were unfamiliar with financial record-keeping or using digital financial applications. The implementation method included initial observations and surveys, program outreach, and hands-on training on the use of the Money Manager application. The results revealed that most participants showed significant improvement in their understanding and ability to record income and expenses, prepare household budgets, and interpret digital financial reports autonomously. This program has proven effective in encouraging the transformation of family financial management habits from manual to digital, positively impacting financial awareness and efforts to improve family welfare.